EFICIÃŠNCIA DO FEROMÃ”NIO DE AGREGAÃ‡ÃƒO E INSETICIDAS QUÃMICOS NO COMBATE AO BICUDO, Anthonomus grandis Boheman, 1843 (Coleoptera; Curculionidae) - Habib, M. E.M.; Fernandes, W. D.; Favaro Jr., A.; Andrade, C. F. S. (REVISTA DE AGRICULTURA, 2015)
EFICIÃŠNCIA DO FEROMÃ”NIO DE AGREGAÃ‡ÃƒO E INSETICIDAS QUÃMICOS NO COMBATE AO BICUDO, Anthonomus grandis Boheman, 1843 (Coleoptera; Curculionidae)